The Impact of Oil Revenue Fluctuations on Private Consumption Expenditures of Non-Durable and Durable Goods in Iran - Yazdan Gudarzi Farahani; Mojtaba Akbari; Omidali Adeli (پژوهش‌های برنامه و توسعه)
The shock of oil revenues, through changes in household expectations, leads to different effects on consumer spending in the durable and non-durable goods sector. Accordingly, the purpose of this article was to investigate the impact of oil revenues on private consumption expenditures of durable and non-durable goods in Iran. To test this relationship, two linear and nonlinear models in the period 1978-2020 were used. The model used in this study was of ARDL and NARDL methods. The results obtained in the estimated linear model showed that the intensity of the effect of disposable income on the consumption expenditure of durable and non-durable goods was equal to 0.61 and 0.68, respectively. Also, the effect of oil revenues on consumption expenditures of durable and non-durable goods in the nonlinear model was equal to 0.68 and 0.53, respectively. Moreover, the results obtained from the analysis of positive and negative shocks showed that the effect of positive shock of oil revenues on the consumption of durable and non-durable goods is 0.47 and 0.21, respectively, and the effect of negative shock of oil revenues on the consumption of goods Durable and non-durable were -0.35 and -0.14, in turn.